Health insurance coverage among women of reproductive age in rural Ghana: policy and equity implications - Martin Ayanore; Agani Afaya; Maxwell Tii Kumbeni; Timothy Tienbia Laari; Bright Opoku Ahinkorah; Solomon Mohammed Salia; Victoria Bam; Vida Nyagre Yakong; Richard Adongo Afaya; Robert Kaba Alhassan; Abdul-Aziz Seidu (BMC, 2023)
Abstract Background Globally, health insurance has been identified as a key component of healthcare financing. The implementation of health insurance policies in low and middle-income countries has led to a significant increase in access to healthcare services in these countries. This study assessed health insurance coverage and its associated factors among women of reproductive age living in rural Ghana. Methods This study used a nationally representative data from the 2017/2018 Ghana Multiple Indicator Cluster Survey (GMICS) and included 7340 rural women aged 15-49 years. Bivariate and multivariable logistic regression models were developed to assess the association between the explanatory and the outcome variable. Statistical significance was considered at p = 0.05. Results The overall prevalence of health insurance coverage among rural women in Ghana was 51.9%. Women with secondary (aOR = 1.72, 95% CI: 1.38-2.14) and higher education (aOR = 4.57, 95% CI: 2.66-7.84) were more likely to have health insurance coverage than those who had no formal education. Women who frequently listened to radio (aOR = 1.146, 95% CI: 1.01-1.30) were more likely to have health insurance coverage than those who did not. Women who had a child (aOR = 1.81, 95% CI: 1.50-2.17), two children (aOR = 1.59, 95% CI: 1.27-1.98), three children (aOR = 1.41, 95% CI: 1.10-1.80), and five children (aOR = 1.36, 95% CI: 1.03-1.79) were more likely to have health insurance coverage than those who had not given birth. Women who were pregnant (aOR = 3.52, 95% CI: 2.83-4.38) at the time of the survey, and women within the richest households (aOR = 3.89, 95% CI: 2.97-5.10) were more likely to have health insurance coverage compared to their other counterparts. Women in the Volta region (aOR = 1.36, 95% CI: 1.02-1.81), Brong Ahafo region (aOR = 2.82, 95% CI: 2.20-3.60), Northern region (aOR = 1.32, 95% CI: 1.02-1.70), Upper East region (aOR = 2.13, 95% CI: 1.63-2.80) and Upper West region (aOR = 1.56, 95% CI: 1.20-2.03) were more likely to have health insurance coverage than those in the Western region. Conclusion Although more than half of women were covered by health insurance, a significant percentage of them were uninsured, highlighting the need for prompt policy actions to improve coverage levels for insurance. It was found that educational level, listening to radio, parity, pregnancy status, wealth quintile, and region of residence were factors associated with health insurance coverage. We recommend better targeting and prioritization of vulnerability in rural areas and initiate policies that improve literacy and community participation for insurance programs. Further studies to establish health policy measures and context specific barriers using experimental designs for health insurance enrolments are required.